Acute Colitis due to Methyldopa - Michael Troster; Stephen N. Sullivan (Canadian Journal of Gastroenterology)
A case of acute colitis due to antihypertensive therapy with methyldopa is reported . The colonic biopsies showed heavy infiltrates of eosinophils with crypt abscesses, cryptitis and vascular cuffing. Cessation of methyldopa therapy relieved the colitis with recurrence after restarting methyldopa on two separate occasions.